2016
DOI: 10.1186/s12889-016-3837-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and patterning of non-communicable disease risk factors in indigenous Mbororo and non-autochthonous populations in Cameroon: cross sectional study

Abstract: BackgroundData on Non-Communicable Diseases (NCDs) among indigenous populations are needed for interventions to improve health care. We conducted a survey in 2013 among rural indigenous Mbororo, Fulbe and other ethnic groups to determine the distribution of risk factors of NCDs in Cameroon.MethodsWe selected seven targets of NCD risk factors: tobacco use, alcohol use, diet (salt/sugar intake, vegetable/fruit consumption), raised blood pressure, raised blood glucose, physical inactivity and weight measures. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Overall, the results of this study is consistent with survey studies in India (Mote, 2016), China (Li et al, 2015), and Cameroon (Kufe, Ngufor, Mbeh, & Mbanya, 2016) which showed regional disparities on the prevalence of NCDs risk factors. These could be associated with the demographics, lifestyle, cultural and social norms, geographic variations and religious influences of a specific region.…”
Section: Discussionsupporting
confidence: 81%
“…Overall, the results of this study is consistent with survey studies in India (Mote, 2016), China (Li et al, 2015), and Cameroon (Kufe, Ngufor, Mbeh, & Mbanya, 2016) which showed regional disparities on the prevalence of NCDs risk factors. These could be associated with the demographics, lifestyle, cultural and social norms, geographic variations and religious influences of a specific region.…”
Section: Discussionsupporting
confidence: 81%
“…Rural settings and lifestyle have been cited as a protection factor to explain the low prevalence of cardiovascular risk and disease in African populations but the Fulani population, as well as the Maasai in Tanzania, showed a high prevalence of hypertension amongst rural dwellers which may not confer the protective possibility. We have reported an increase in the prevalence of NCD risk factors as a nomadic pastoral Fulani transition to settled life as well as differences in anthropometric and lifestyle factors by ethnicity [ 10 ]. The Kenyan Luo Migration Study also showed an increase in blood pressure following rural-urban migration [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1337 Fulani or Peul aged ≥ 20 years from 555 households were recorded with complete data and included in this analysis. The details of the population are in our previous paper [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations